(untitled) (Global Journal of Management and Business Research, 2013)
University business education graduates, by the nature of their programme, ought to possess relevant information and communication technology competencies for successful entrepreneurship but casual observation and empirical reports indicate that they are not doing well in this aspect. Therefore, this study assessed the ICT competencies possessed by the university postgraduate business education students to handle entrepreneurship business challenges in Nigeria. One research questionand five hypotheses guided the study. Descriptive survey design was adopted for the study. The population, also used as the sample, consisted of 388 business education graduates who are currently running their postgraduate programme in universities in the south-south and south-east geopolitical zones. A validated questionnaire with a reliability coefficient of 0.96 was used for data collection. The mean and standard deviation were used to analyze the research questions while Z-test was used to test the hypotheses at 0.05 level of significance. The results revealed that the respondents have relevant competent in ability to send e-mail, ability to receive e-mail, skills in producing documents with word processors among others. However, it was recommended that university authorities should encourage business education lecturers and students to organize workshops and conferences with a view to keeping them abreast to acquire more skills in ability to receive and send fax messages and ability to create website.